(untitled) (Swiss Medical Weekly, 2012)
AIM OF THE STUDY: In Switzerland, screening concepts for the prevention of sports-associated sudden cardiac death are still insufficiently established in the large group of competitive athletes who are not integrated in an Olympic- or other high-level squad. The aim of the present study was to objectively determine the current situation in this particular group of athletes concerning cardiac pre-competition screening and define specific features of an “ideal” Swiss screening concept. Based on these data, the feasibility and validity was tested by the implementation of an exemplary local screening programme. METHODS: A standardised questionnaire was completed by 1,047 competitive athletes of different ages and gender. The individual, sports-specific profile of an athlete and furthermore, the personal attitude towards and the vision of a “perfect” cardiac screening were assessed. Based on the results, an exemplary local screening programme for competitive athletes was implemented at the “Academic Sports Association Zurich” (ASVZ) in Zurich, Switzerland and evaluated 1 year after its introduction. RESULTS: Only 9% of the 1,047 interviewed competitive athletes (aged 13 to 64 years; median age 22 years, SD = 5.87) had previously undergone a cardiac screening. Only 47% of the interviewed competitive athletes expressed their interest to undergo a cardiac screening at all. Male and older athletes showed a significantly higher acceptance rate for the screening programme than women and younger athletes. All athletes accepted to bear the expenses for the baseline screening programme, adapted to international standards (minimal accepted fee of 60 Swiss Francs). Almost half of the athletes (49.2%) preferred easy accessibility to a sports cardiologist (max. distance of 10 kilometres). The exemplary local screening programme proved to be feasible and successful. However, only 30% of the 102 screened individuals were female and most of the athletes (80%) who made use of the screening had a specific concern or symptom (selection bias). A total of 5 athletes (4.9%) were, at least temporarily, declared as not eligible for competitive sports due to a relevant cardiac pathology. CONCLUSION: The fact that only 9% of the interviewed competitive athletes had previously undergone cardiac screening is alarming, but underlines the necessity and urgency of implementing a cost-effective and adequate screening concept in the enormous group of competitive athletes who are not integrated in an Olympic- or other high-level squad. The need for a certain self-determination and personal responsibility of the athletes should be respected. Therefore, the screening should not be mandatory. However, adequate information about the issue is crucial for an informed decision.